Transformasi Digital dalam Mewujudkan Pelayanan Kesehatan yang Prima di Rumah Sakit Jiwa Tampan Provinsi Riau - Ruqayah Qisthijahraa; Tamba Togap Tambun; Harapan Tua R.F.S (Lembaga Yasin AlSys, 2025)
Digital transformation is a strategic necessity for improving the quality of health services in the modern era. This study aimed to analyze the implementation of digital transformation at Rumah Sakit Jiwa (RSJ) Tampan, Riau Province, which has adopted various innovations such as the Hospital Management Information System (SIMRS), the SITAMPAN online registration service, and employee attendance based on electronic signatures, as well as to examine their contribution to the realization of excellent health services. A descriptive qualitative approach was employed through interviews, field observations, and document analysis with informants comprising healthcare workers, administrative staff, and management. The findings show that digitalization has accelerated the registration process, facilitated access to information, improved data accuracy, and strengthened transparency and work efficiency, which in turn has enhanced patient satisfaction through faster, more accurate, and more responsive services. However, the study also identified obstacles, including unstable internet connectivity, limited devices, and varying levels of employees’ digital literacy, which hinder optimal system utilization. Overall, digital transformation at RSJ Tampan has made a positive contribution to realizing excellent health services and strengthening accountability and public trust, with implications for the need to improve technological infrastructure and provide continuous training programs so that digitalization can proceed more optimally and sustainably in the future.